Radiometric survey on the exposure to and management of radioactive waste produced by patients on I131 treatment - Santos, Elsom José Gomes; Couto, Alessandra Sampaio; Martins, Higor Leonardo Gomes Santos; Martins, Letícia Stella Gomes Santos; Gomes, Wolia Costa (Ciência e Natura, 2018)
The objective of this study is to perform a radiometric survey on the exposure of Occupationally Exposed Individuals (OEI) to radioactive waste and to evaluate the management of radioactive waste produced by patients treated with Iodine-131 (I131) in a hospital in São Luís, MA, Brazil. For this purpose, radiometric levels were measured using radiation measuring devices placed at strategic points in the hospital bed and the areas surrounding the tailings deposit. For four months, a team of professionals using equations of exposure rate, activity, and equivalent dose analyzed the waste disposal management and the exposure received by the OEI. It was concluded that the discarded waste had a level lower than 2 μCi/kg, thus complying with CNEN 6.05 standard. Patients who were administered I131 with 100 and 150 mCi activity needed to be hospitalized for only 24 hours, while those with 200 mCi activity required 36 to 48 hours of hospitalization. The exposure rate emitted by the wastes in the iodine rooms was 1.95 mR / h and in the area near the tailings deposit, the OEI received an equivalent dose of 0.01 mSv per week - values below the maximum limit allowed by CNEN 3.01/2014.